Analysis of Factors that Influence Economic Growth and Regency/City Poverty in Bali Province - Arta, I Wayan Yoniga; Budhi, Made Kembar Sri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Economic growth is an important benchmark in determining the success of economic development. The most important goal of development is reducing the level of poverty which can be achieved through economic growth. The aim of the research is to analyze the direct and indirect influence of exogenous variables and endogenous variables. The object of this research is economic growth and poverty levels in districts/cities in Bali Province which are influenced by factors such as educational level variables, local income, working population, and investment. The number of observations in the research was 45 observation points, consisting of 9 districts/cities in Bali Province over a period of 5 years, namely 2018 - 2022. The data analysis technique used in this research is path analysis. The results of this research show that: (1) The level of education, working population, and investment have a significant positive effect, while MSEs have a significant negative effect on the economic growth of districts/cities in Bali Province; (2) The level of education, UMK, and economic growth have a significant negative effect on the poverty level of districts/cities in Bali Province, while the working population has a positive and insignificant effect and investment has a positive and significant effect on the poverty level of districts/cities in Bali Province; (3) Education level, UMK, working population, and investment have an indirect effect on poverty levels through the economic growth of districts/cities in Bali Province.